Real-world assessment of effectiveness and safety of filgotinib in 286 patients with ulcerative colitis in 9 UK centres - David Young; Sohail Rahmany; Deborah Taylor; Emma Davis; Michael Colwill; Sonia Kalyanji Mehta; Roisin Campbell; Karl Hazel; Karishma Sethi-Arora; Susan Ritchie; Ashley I Heinson; Helen Moyses; et al. (Drugs in Context)
Background: Filgotinib, an oral Janus kinase 1 preferential inhibitor, has been shown to be an effective treatment for ulcerative colitis (UC) in pre-registration studies. We aimed to describe the treatment population, effectiveness and safety of filgotinib in a real-world cohort of patients with UC.